Studies on in Vitro Propagation and Genetic Transformation Protocol of Apple Rootstock M7 - Mehta, Kirti (My University, 2012)
The present study was an attempt to develop the shoot regeneration and genetic transformation protocol for apple rootstock M7. Impact of medium composition (mineral nutrients, different combinations of plant growth regulators) on shoot multiplication, callusing, regeneration and rooting of apple rootstocks cultured on Murashige and Skoog (MS) medium were investigated. The best shoot prolification in terms of shoot number and shoot quality was obtained using 2.5 µM 6-benzylaminopurine (BAP) and 1.0 µM Naphthaleneacetic acid (NAA) during the shoot multiplication phase. The rooting of microshoots were induced by indole-3-butyric acid (IBA) and best rooting was achieved on MS medium containing 5 µM IBA. Shoot regeneration was observed 5-6 weeks after subcultured on MS medium supplemented with 5.0 µM BAP and 5.0 µM NAA. In vitro produced leaves of the apple rootstock M7 were infected with Agrobacterium tumefaciens strains containing a binary vector carrying the nptII gene and the uidA gene on the T-DNA. The effect of different parameters on transient GUS expression after two days of co-cultivation with Agrobacterium was studied. Co-cultivation period of 2 days and a bacterial density of 0.6 OD600 resulted in higher transient GUS expression in explants. The clonal fidelity of micropropagated shoots were established using Random Amplified Polymorphic DNA (RAPD) and Inter Simple Specific Repeats (ISSR) markers.
Keywords: Micropropagation; Transformation; Apple root stock